FOUR-TIER DIAGNOSTIC TEST TO IDENTIFY MISCONCEPTIONS IN GEOMETRICAL OPTICS - Fariyani, Qisthi; Rusilowati, Ani; Sugianto, Sugianto (Unnes Science Education Journal, 2017)
The purpose of this research was to identify student misconceptions in Geometrical Optics. Four-tier multiple choice diagnostic test can be used to identify student misconceptions. The data of this research were obtained by interview, questionnaire, and test. This research used random sampling to 107 X grade students who already got Geometrical Optics materials. The data of this research were analyzed and interpreted to distinguish students who understand the concept, not understand, and misconceptions. The result of the research showed that on each item of the test, there are some students who have misconceptions. Students had misconceptions in the low category with details of 31% of all test item, 53% in the medium category, and 16% in the high category.